The value of loop-mediated isothermal amplification in diagnosing lower respiratory tract infections in children - Yan, Feng; Xu, Shikun; Shen, Meijing; Zhao, Yu; Tong, Huabo; Wu, Kaifeng; Zha, He (Practical laboratory medicine, 2025)
To evaluate the diagnostic value of loop-mediated isothermal amplification(LAMP) chip method (hereinafter referred to as "LAMP") in the detection of pathogens in children with lower respiratory tract infections(LRTIs). Sputum samples from 1723 children with LRTIs hospitalized from April 2020 to April 2021 were collected. Pathogen detection was performed using both LAMP and sputum culture method(SCM).Detection rates and consistency between the two methods were analyzed using the Chi-square test and Kappa analysis. The positive detection rates of the LAMP and the SCM were 58.97 %(1016/1723) and 43.64 %(752/1723), respectively(P<0.001). The detection rates of Streptococcus pneumoniae (Spn)(24.26 %/13.52 %), Staphylococcus aureus(Sau)(13.12 %/10.39 %), Acinetobacter baumannii (Aba)(1.33 %/0.48 %), Stenotrophomonas maltophilia (Sma)(0.58 %/0.12 %), and Haemophilus influenzae(Hin)(31.05 %/16.19 %) were significantly higher with the LAMP than with the SCM(P<0.05). Both methods showed that single infections were predominant among children, with positive rates of 65.06 % and 87.23 %, respectively, with Hin(49.92 %/33.69 %) being the most common pathogen.In mixed infections, the positive rates were 34.94 % and 12.77 %, respectively, with mixed infections of Hin and Spn being the most common, accounting for 48.89 % and 32.29 % of cases, respectively. There were significant differences in the detection rates of Spn, Sau, Klebsiella pneumoniae(Kpn), Sma, Hin, and Escherichia coli(Eco) between single and mixed infections(P < 0.05). The detection results of Spn, Sau, Kpn, Hin, and Eco exhibited high consistency between the two methods, while the consistency for Pseudomonas aeruginosa(Pae), Aba, and Sma was lower. The LAMP is simpler, faster, more sensitive and specific than SCM, offering a reliable laboratory diagnostic basis for clinical management of LRTIs in children. •Children who had contracted lower respiratory tract infections(LRTIs) were chosen as the research subjects.•The whole process of Loop-mediated Isothermal Amplification(LAMP), spanning from sample analysis to result interpretation, can be completed within 1–2 h.•A total of 1723 sputum samples were analyzed to assess the consistency between Loop-mediated Isothermal Amplification(LAMP) and Standard Culture Method(SCM).